The PNR to relaxor transition in PSN with nearest neighbor Pb-O divacancies. (26th October 2018) - Burton, B. P.; Cockayne, Eric; Gopman, D.; Dogan, G.; Hood, Sarah
Abstract: In previous work, molecular dynamics simulations based on a first-principles-derived effective Hamiltonian for Pb1-X (Sc1/2 Nb1/2 )O3-X (PSN), with nearest-neighbor Pb-O divacancy pairs, was used to calculate X[Pb-O] vs. T, phase diagrams for PSN with: ideal rock-salt type chemical order; nanoscale chemical short-range order; and random chemical disorder. Here, we show that the phase diagrams should include additional regions in which a glassy relaxor-phase (or state) is predicted. With respect to phase diagram topology, these results strongly support the analogy between relaxors and magnetic spin-glass-systems.